2021
DOI: 10.1080/01446193.2021.1913285
|View full text |Cite
|
Sign up to set email alerts
|

How relational contract theory influence management strategies and project outcomes: a systematic literature review

Abstract: Despite growing interest in Relational Contracting (RC), few studies have comprehensively investigated the qualities required for a successful RC project. Macneil's ten norms are principles of behaviour in contracts based on the application of relational contract theory and play an essential role in the formation and agreement of parties and their commitment to means and objectives. In contributing a missing dimension to the RC approach in construction, the purpose of this research is to conduct a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 78 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…To conclude, internal auditors adopt a number of measures to establish and maintain a trusted relationship with management. Although the IAF is governed by formal terms of contract (e.g., a charter), internal auditors use various measures and strategies to establish informal relational contracts, which promote creativity, flexibility, trust, open communication, information sharing, and cooperation (Nwajei, 2021), thereby reducing conflict and improving output—that is, audit effectiveness. However, corporate culture may affect management's approach towards the IAF, its status within the organisation, its importance as a corporate governance mechanism and managements' tendency to accept change (Trotman & Duncan, 2018).…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…To conclude, internal auditors adopt a number of measures to establish and maintain a trusted relationship with management. Although the IAF is governed by formal terms of contract (e.g., a charter), internal auditors use various measures and strategies to establish informal relational contracts, which promote creativity, flexibility, trust, open communication, information sharing, and cooperation (Nwajei, 2021), thereby reducing conflict and improving output—that is, audit effectiveness. However, corporate culture may affect management's approach towards the IAF, its status within the organisation, its importance as a corporate governance mechanism and managements' tendency to accept change (Trotman & Duncan, 2018).…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…(2021) showed that RC reduces in formation asymmetry in construction projects by 85%. Nwajei (2021) also pointed out how RC theory influences management strategies and project consequences. Notwithstanding these positive results, the question as to how mitigation of contractual breaches may be effected remains unanswered.…”
Section: Introductionmentioning
confidence: 99%